Reputation: 505
I am trying to implement a Functor instance of
data ComplicatedA a b
= Con1 a b
| Con2 [Maybe (a -> b)]
For Con2, my thought process was the fmap needs to be something like
fmap f (Con2 xs) = Con2 (map f' xs)
then I need to have a list map function f' like
Maybe (a -> x) -> Maybe (a -> y)
Since Maybe
is a Functor, I can write f' like
fmap ((a->x) -> (a->y))
In order to get ((a->x) -> (a->y))
, I thought I could just do
fmap (x->y)
which is the same as (fmap f)
So my sulotion was
instance Functor (ComplicatedA a) where
fmap f (Con1 x y) = Con1 x (f y)
fmap f (Con2 xs) = Con2 (map (fmap (fmap f)) xs)
However the real solution uses (f .)
instead of (fmap f)
to get ((a->x) -> (a->y))
from x -> y
and it looks like this
instance Functor (ComplicatedA a) where
fmap f (Con1 a b) = Con1 a (f b)
fmap f (Con2 l) = Con2 (map (fmap (f .)) l)
I was just wondering what the problem was with my thought process and solution. Is (fmap f) the same as (f .) if f is a function of type a->b?
Thank you in advance.
Upvotes: 7
Views: 208
Reputation: 34378
The solutions are indeed equivalent. fmap
for the function/reader functor is (.)
:
instance Functor ((->) r) where
fmap = (.)
((->) r
is the function type constructor being used with prefix syntax -- (->) r a
is the same as r -> a
.)
The intuition is that, as you have noted, (.) :: (x -> y) -> (a -> x) -> (a -> y)
uses a x -> y
function to modify the results of an a -> x
function.
Upvotes: 6